Overview of the Study of Philosophy in Overcoming Anxiety in Pregnant Women at the Time of Delivery at the RSUD dr. Chasan Boesoerie Ternate City - Nursia Aja; Suryo Ediyono (CV. Inara, 2022)
Anxiety is a normal condition that may be felt by every pregnant woman if there is a soul that experiences pressure or feelings of anxiety that are so deep that it can cause psychiatric problems. Anxiety often develops in the long term and largely depends on one's entire life experience. Methods: This study is an observational analytical study with a cross-sectional study to describe the anxiety of pregnant women and to assess several features of philosophical studies in dealing with pregnant women. at the time of delivery. The population in this study were all pregnant women who were recorded in the register book and the MCH visit book for pregnant women at the RSUD Dr. Chasan Basoeri during 2020. The sampling technique was carried out using the total sample method. The research was conducted from November to December 2020. The results obtained in the variables: Age of pregnant women was 71.2%, education level was 59.3%, mother's knowledge was 67.8%, feeling of undergoing labor was 63.4 %, information from health workers was 67.8%, husband's support was 54.2% and mother's anxiety level was 67.8%. Conclusion: it is necessary from the Hospital dr. Chasan Boesoerie always provides information and counseling about pregnant women, and always provides information to husbands about health information for pregnant women and can visit or check pregnancy in K4, so as to avoid the level of anxiety of pregnant women during childbirth, especially in hospitals and health centers in Ternate City.